RISK FACTORS FOR THE FORMATION OF THE REPRODUCTIVE HEALTH OF ADOLESCENT GIRLS - Кох, Лилия Ивановна; Бурцева, Галина Анатольевна (Mother and Baby in Kuzbass, 2017)
The risk factors for the formation of the reproductive health of adolescents studied on the basis of a comprehensive survey of 155 girls aged 15-16 years. The influence of traditional factors (ante- and postnatal periods, early childhood), the state of physical, gynecological health, behavioral, social status. Using a special questionnaire studied the level of personal and reactive anxiety level of neuroticism. Based on these results, it was proved that various disorders in the development of reproductive health of adolescents may play the role of unfavorable factors, beginning with the ante and post-natal development, and particularly social and psychological situation in which the girl is growing.
Keywords: adolescent girls; reproductive health; risk factors